Associations of anticoagulant use with outcome in newly diagnosed glioblastoma - Le Rhun, Emilie; Wick, Wolfgang (European journal of cancer, 2018)
Background - To test the hypothesis that despite bleeding risk, anticoagulants improve the outcome in glioblastoma because of reduced incidence of venous thromboembolic events and modulation of angiogenesis, infiltration and invasion. - Methods - We assessed survival associations of anticoagulant use from baseline up to the start of temozolomide chemoradiotherapy (TMZ/RT) (period I) and from there to the start of maintenance TMZ chemotherapy (period II) by pooling data of three randomised clinical trials in newly diagnosed glioblastoma including 1273 patients. Progression-free survival (PFS) and overall survival (OS) were compared between patients with anticoagulant use versus no use; therapeutic versus prophylactic versus no use; different durations of anticoagulant use versus no use; anticoagulant use versus use of anti-platelet agents versus neither anticoagulant nor anti-platelet agent use. Cox regression models were stratified by trial and adjusted for baseline prognostic factors. - Results - Anticoagulant use was documented in 75 patients (5.9%) in period I and in 104 patients (10.2%) in period II. Anticoagulant use during period II, but not period I, was associated with inferior OS than no use on multivariate analysis (p = 0.001, hazard ratio [HR] = 1.52, 95% confidence interval [CI]: 1.18-1.95). No decrease in OS became apparent when only patients with prophylactic anticoagulant use were considered. No survival association was established for anti-platelet agent use. - Conclusions - Anticoagulant use was not associated with improved OS. Anticoagulants may not exert relevant anti-tumour properties in glioblastoma.
Gesehen am 25.02.2020